2019
DOI: 10.1039/c8nr08760a
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchically hydrogen-bonded graphene/polymer interfaces with drastically enhanced interfacial thermal conductance

Abstract: Hierarchically hydrogen-bonded interface was designed to drastically enhance the interfacial thermal conductance between materials of drastically different vibrational properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 65 publications
2
29
0
Order By: Relevance
“…It is well established that TBC depends on the bonding strength at the interface, which has been predicted by analytical models [36], molecular dynamics simulations [37][38][39][40][41] and experiments [42][43][44][45]. In this study, the observed increase in G is most likely caused by an increase in adhesion between the metal and polymer.…”
Section: Resultssupporting
confidence: 54%
“…It is well established that TBC depends on the bonding strength at the interface, which has been predicted by analytical models [36], molecular dynamics simulations [37][38][39][40][41] and experiments [42][43][44][45]. In this study, the observed increase in G is most likely caused by an increase in adhesion between the metal and polymer.…”
Section: Resultssupporting
confidence: 54%
“…These studies have investigated the effects of various characteristics of SAMs on the interfacial thermal conductance from two different points of view: (1) considering accurate information about SAM, including SAM coverage [4,9,10], length of SAMs [4,[11][12][13], distinct functional group [9,[13][14][15][16][17], heterogeneous fin structure [18], vibrational spectral overlapping [9], nanoscale roughness [19][20][21], and so on. Huang et al [16] investigated interfacial thermal conductance (ITC) across the interface of water and gold tailored with -CH 3 SAM, -OHSAM, and -COOHSAM.…”
Section: Introductionmentioning
confidence: 99%
“…The first candidate that came to mind was poly(vinyl alcohol) (PVA, [-CH 2 -CHOH-] n ), because its melting point is above 200 1C 17,18 and it introduces only a minor change in the carbon chain of PE ([-CH 2 -CH 2 -] n ) by replacing a hydrogen (-H) with a hydroxyl (-OH) 19 in each segment. The literature 20,21 shows that this replacement should result in the evolution of a phonon dispersion curve (Fig.…”
Section: Introductionmentioning
confidence: 99%